2019
DOI: 10.1103/physrevb.99.224203
|View full text |Cite
|
Sign up to set email alerts
|

Many-body localization in the presence of long-range interactions and long-range hopping

Abstract: We study many-body localization (MBL) in a one-dimensional system of spinless fermions with a deterministic aperiodic potential in the presence of long-range interactions or long-range hopping. Based on perturbative arguments there is a common belief that MBL can exist only in systems with short-range interactions and short-range hopping. We analyze effects of power-law interactions and power-law hopping, separately, on a system which has all the single particle states localized in the absence of interactions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 82 publications
3
49
1
Order By: Relevance
“…On the other hand, low entanglement and nonergodic behaviors, which are different from many-body localization, have been found in a nearest-neighbor model with SU(2) symmetry [16,17]. There were several studies investigating whether many-body localization can survive in the presence of different types of long-range terms in the Hamiltonian [33][34][35][36] since one might expect that long-range terms will increase the amount of entanglement. Similarly, it is unclear whether nonlocal terms will destroy the nonergodic, low entanglement behavior seen in local models with SU(2) symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, low entanglement and nonergodic behaviors, which are different from many-body localization, have been found in a nearest-neighbor model with SU(2) symmetry [16,17]. There were several studies investigating whether many-body localization can survive in the presence of different types of long-range terms in the Hamiltonian [33][34][35][36] since one might expect that long-range terms will increase the amount of entanglement. Similarly, it is unclear whether nonlocal terms will destroy the nonergodic, low entanglement behavior seen in local models with SU(2) symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently much interest in finding out how nonlocal terms in a Hamiltonian affect the thermalization properties of a system [33][34][35][36], e.g., whether many-body localization is possible when different types of long-range terms are present, as one might expect that long-range terms could increase the amount of entanglement. As mentioned above, it has been argued that systems with SU(2) symmetry cannot many-body localize since SU(2) symmetry is incompatible with area law scaling of the entanglement entropy [14,15], and it is hence expected that we do not find many-body localization in the studied, nonlocal model.…”
Section: Introductionmentioning
confidence: 99%
“…Another intriguing question is how the interplay between partial correlations in hopping and interaction amplitudes could affect localization properties in many-body systems with either or both hopping and interaction terms being longranged in the coordinate space. Specifically, the limiting fullycorrelated case of the interacting version of Burin-Maksimov model was recently analyzed in [60,[72][73][74][75][76], and the opposite situation without any constraints was considered in details in [77][78][79][80][81][82]. However, the intermediate regime represented by both finite means and dispersion in distribution functions of matrix elements needs deep consideration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, other theoretical frameworks used for disordered spin chain has shown the existence of MBL for strong LRI [36]. More recently, Nag and Garg [37] demonstrated that MBL persists in the presence strong long-range hopping. They studied a one-dimensional system of spinless fermions with a deterministic aperiodic potential in the presence of long-range interactions and long-range hopping.…”
Section: Introductionmentioning
confidence: 99%